Respectful Transgressions of Common Law and Civil Law Teaching in Quebec: Lessons from the Transsystemic Method of Legal Education - Córdova Flores, Álvaro (2023)
This article explores how the law is taught in the bi-juridical order of Quebec, where civil law and common law coexist. It focuses mainly on how the trans-systemic method of legal education was implemented and developed at the Faculty of Law of McGill University, in Canada. This method consists of teaching both legal traditions simultaneously and comparatively. It aims to enable its graduates to navigate Canada’s political and cultural tensions, engage in cross-cultural legal dialogues and practice in two legal systems. This approach emphasizes the coexistence of two legal systems, moving away from legalistic views and embracing legal pluralism. The article explains the different contextual layers surrounding the emergence and development of this trans-systemic method. It explains the macro-institutional context by presenting the tensions between Anglo-Canada and the province of Quebec; the meso-institutional context, which focuses on the discussions within the province and the law faculty; while the micro-institutional context presents how courses on obligations/contracts and tort/torts are taught.